Targeting technology to reduce poverty and conserve resources: Experimental delivery of laser land leveling to farmers in Uttar Pradesh, India - Lybbert, Travis J.; Magnan, Nicholas; Spielman, David J.; Bhargava, Anil K.; Gulati, Kajal (International Food Policy Research Institute, 2013)
Demand heterogeneity often makes it profitable for firms to price and promote goods and services differently in different market segments. When private consumption brings public benefits, this same heterogeneity can be used to target public subsidies. We explore the design of public–private targeting and segmentation strategies in the case of a resource-conserving agricultural technology in India. To understand farmers’ heterogeneous demand for laser land leveling (LLL), we conducted an experimental auction for LLL services with an integrated randomized controlled trial to estimate the private benefits of the technology. We use graphical and econometric approaches to characterize farmer demand for LLL. We then add detailed cost data from LLL providers to simulate and evaluate several potential targeted delivery strategies based on measures of (1) the cost-effectiveness of expanding LLL dissemination, (2) water savings, and (3) market surplus in a welfare framework. These simulations demonstrate inherent tradeoffs between increasing the amount of land that is leveled and expanding the number of farmers who adopt the technology, and between adoption and water savings. While segmenting and targeting are popular elements of many public–private partnerships to develop and disseminate agricultural technologies, formulating and implementing effective delivery strategies requires a rich understanding of costs, benefits, and demand. Our experimental approach generates such an understanding and may be relevant in other contexts.